Analysis of the scientific collaboration patterns in the Emergy Accounting field: A review of the co-authorship network structure - Liu, Gengyuan; Yang, Zhifeng; Chen, Bin; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Using Social network analysis techniques, the authors visualize the co-authorship network and provide descriptive statistics regarding the degree to which researchers are embedded in it. The aim of this paper is to point out three issues including: (1) the use and quantification of international bibliographic databases; (2) Social Network Analysis and interpreting merits; and (3) visualization and the analysis of coauthorship networks for co-authorship data. The results showed that there was a strong linear relationship between the number of papers published and an author’s h-index. And the co-author network displayed the following features: with medium connected groups of authors; the network density is low; many sparse ties since there are still observed isolated authors or simple clusters in the network; and a medium propensity to collaborate with co-authors. Such an understanding is a necessary pre-requisite to establish an information flow and collaboration pattern among authors involved in the progress of the emergy accounting field.